History and Existence of Sanghyang Janger Maborbor Dance in Bangli - Nyoman Sabda (Bali Tourism Board, 2024)
In Indonesia, dance serves both artistic and religious functions, particularly in religious ceremonies. This is exemplified in the village of Yangapi, located in the Tembuku district of Bangli Regency. Beyond its well-known waterfall tourism, this village maintains a rich cultural tradition in the form of Janger Maborbor sacred dance. This dance is considered unique due to its religious function, which is closely tied to the local belief system, particularly in its role as a medium for connecting with astral entities. This study aims to examine the ongoing existence of Janger Maborbor sacred dance in Yangapi village as an integral part of Balinese culture that has endured to the present day. This research employs a qualitative descriptive research method. Data collection is conducted through field observations and interviews. The findings are presented in textual form, supplemented by visual documentation as supporting evidence. During the performance of the Sanghyang Janger Maborbor Dance, transcendental communication takes place in the form of a dialogue between humans and the Divine. This dialogue is expressed through sacred mantras and prayers recited by the temple priest (pemangku), as well as through the trance-induced (kerauhan) movements of the dancers. Additionally, offerings (banten) serve as a symbolic expression of devotion and gratitude to God. Through this sacred communication, Hindu devotees and all those involved in the performance of the Sanghyang Janger Maborbor Dance experience a spiritual closeness with the Divine.